Quantification of Zn2+ Ion in Environmental Samples by Fabrication of Pyrolytic Graphite Electrode Based on Schiff Bases of Hydrazinecarbothioamide Derivatives. Issue 9 (1st January 2017) - Sahani, Manoj Kumar; Singh, A. K.; Jain, A. K.
Abstract : Schiff base ligands 2, 2 ′ -(((ethane-1, 2-diylbis(oxy))bis(2, 1-phenylene))bis(methanylylidene))bis(hydrazinecarbothioamide) (L1 ), 2, 2 ′ -(((propane-1, 3-diylbis(oxy))bis(2, 1-phenylene))bis(methanylylidene))bis(hydrazinecarbothioamide) (L2 ) and 2, 2 ′ -((((oxybis(ethane-2, 1-diyl))bis(oxy))bis(2, 1-phenylene))bis(methanylylidene))bis(hydrazinecarbothioamide) (L3 ) have been synthesized and were explored as ion carrier in the construction of solid contact Zn 2+ PVC based membrane sensor. The effect of plasticizers, benzylacetate (BA), dioctylphthalate (DOP), dibutylphthalate (DBP), 1-chloronaphthlene (1-CN) and o -nitro-phenyloctylether ( o -NPOE) and anion excluders, sodium tetraphenylborate (NaTPB) and potassium tetrakis-p-(chlorophenyl)borate (KTpClPB) on the performance of the electrodes has also been investigated. Comparative studies performed on coated graphite electrode (CGE) and coated pyrolytic graphite electrode (CPGE) reveal the superiority of CPGE with optimized membrane composition of L2 : PVC: DOP: NaTBP≡6:34:58:2 (w/w, mg) exhibits the best results with a wide working concentration range of 1.1 × 10 −8 –1.0 × 10 −1 mol L −1, detection limit of 8.0 × 10 −9 mol L −1, Nernstian slope of 29.6 ± 0.2 mV decade −1 of activity of Zn 2+ ion in the pH range of 3.0–9.0. The sensor showed fast response time of 10 s and could be used over a period of 4 months without any significant divergence in slope, working concentration range and detection limit. The sensor was employed in the quantification of Zn 2+ ion in various samples and also as an indicator electrode in the potentiometric titration of Zn 2+ ion with EDTA.